Study on Failure Difference of Hard Rock Based on a Comparison Between the Conventional Triaxial Test and True Triaxial Test - Zheng, Guoqiang; Tang, Yonghui; Zhang, Yan; Gao, Yaohui; Zhu, Guoqiang; Gao, Meiben; Ren, Junqian; Chen, Kezhu; Sun, Jicheng (Frontiers in Earth Science, 2022)
The study on the failure difference of deep hard rock based on comparison between conventional and true triaxial tests can make us better understand the fracture processes and failure characteristics of deep rock mass. Therefore, this paper carries out the comparative analysis on the failure of hard rock under conventional and true triaxial stress states. Within the scope of this study, it is found that the brittle-ductile transformation properties can be intuitively reflected from the rock stress–strain curve and failure mode. The brittle-ductile transition point of rock can also be determined by the difference between peak and residual strengths. The rock failure strength increases with the increase of σ2, the peak strain decreases with the increase of σ2, the stress-drop of the post-peak curve becomes more obvious with the increase of σ2, and the rock tends to Class II brittle failure after the peak with the increase of σ2. When σ3 is relatively high, the rock fracture angle increases with the increase of σ2 with obvious regularity. Compared with conventional triaxial stress condition, the differential stress-induced anisotropy failure is the biggest difference of rock fracture characteristics between true and conventional triaxial stress state. This study can supply useful reference to the study of failure properties of hard rock under complex stress state.